(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This study contrasts some of Shakespeare’s women characters with theirequivalents in the sources from which the plays are drawn. It attempts to givereplies to these inquiries: how did he adjust the characters from the hotspotsfor his plays; how did he pick to act for them: how do his women characterscontrast and pictures of ladies around then?